Power Switching Device Losses - Simulation and Non-Simulation Methods of Calculations - Mohanram, Sat; Darwish, Mohamed; Marouchos, Christos (My University, 2018)
In the design and manufacture of power supplies and converters, commercial factors demand high efficiency figures in the operation and performance of these products. Potential loss areas in the circuits are identified to achieve minimum losses [1] [2]. One of the main component contributing to losses in converters is the switching device.The methods to calculate switching loss [3] are complex and involves several related parameters [4] [5]. Conduction loss, radiation interference [6] and temperature rise, impacts on design efficiency. Depending on the design limitations, a balance between the related parameters is necessary, which can be achieved by optimization processes. The method of linear approximation has useful deductions in the control of turn-on switch loss, choosing switches devices with short switching times, which offers high operating frequencies.
Keywords: Hard switching; Input-output parameters; Losses; Simulation and Non-Simulation Methods; Switching Devices